Forest genetic resources conservation and management: Status in seven South and Southeast Asian countries - Jalonen, R.; Choo, K.Y.; Hong, L.T.; Sim, H.C. (2009)
This compilation of the national status reports from the seven participating countries of the ITTO Project is thesecond joint documentation of national activities for the conservation and management of forest genetic resources in South and South-east Asian countries. The reports in this publication were provided by the National Focal Points of the ITTO project countries during the years 2007-2009, and they capture updates in the conservation and management activities and initiatives in the project countries since the inception workshop of the APFORGEN Programme in 2003. The implementation of the ITTO project is supported by FRIM, in collaboration with APAFRI and Bioversity International.